A retrospective study of blood transfusion practices in obstetrics at Hassan Institute of Medical Sciences - H. N., Poornima; V., Nayanashree; G. V., Ranjitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Blood transfusion is an integral component of obstetric care and an important indicator of maternal morbidity management. Obstetric hemorrhage remains a leading cause of maternal mortality worldwide. Common causes of transfusion in obstetrics include postpartum hemorrhage, antepartum hemorrhage, abortion, ectopic pregnancy, anemia, and coagulation disorders. Evaluating transfusion practices helps assess institutional quality of care. Methods: A retrospective analysis was conducted of obstetric patients admitted to the OBG Department at Hassan Institute of Medical Sciences from 2021–2022. Data were obtained from blood transfusion registers, ICU and HDU admission records, anemia registers, and complication registers to evaluate transfusion indications and patterns. Results: A total of 475 patients in 2021 and 435 in 2022 required blood transfusion, showing an 8.4% reduction in 2022. Anemia in pregnancy was the leading indication (39.8% in 2021; 36.8% in 2022), followed by abortion (22.9% and 25.3%). Postpartum hemorrhage accounted for 10.7% and 10.1% of cases, respectively. Overall, 706 units of blood products were transfused in 2021 compared to 649 units in 2022. Packed red blood cells constituted the majority of transfusions (78.7%), followed by platelet concentrates (10.2%) and fresh frozen plasma (8.6%). Conclusions: Maternal anemia and obstetric hemorrhage remain the predominant indications for transfusion. Strengthening antenatal anemia management, early risk identification, and appropriate blood component therapy are essential to further reduce transfusion requirements and improve maternal outcomes.